Photophysical Study on the Rigid Pt(II) Complex [Pt(naphen)(Cl)] (Hnaphen = Naphtho[1,2-b][1,10]Phenanthroline and Derivatives - Maren Krause; Iván Maisuls; Stefan Buss; Cristian A. Strassert; Andreas Winter; Ulrich S. Schubert; Shruthi S. Nair; Benjamin Dietzek-Ivanšić; Axel Klein (Molecules, 2022)
The electrochemistry and photophysics of the Pt(II) complexes [Pt(naphen)(X)] (Hnaphen = naphtho[1,2-b][1,10]phenanthroline, X = Cl or C≡CPh) containing the rigid tridentate C^N^N-coordinating pericyclic naphen ligand was studied alongside the complexes of the tetrahydro-derivative [Pt(thnaphen)(X)] (Hthnaphen = 5,6,8,9-tetrahydro-naphtho[1,2-b][1,10]phenanthroline) and the N^C^N-coordinated complex [Pt(bdq)(Cl)] (Hbdq = benzo[1,2-h:5,4-h’]diquinoline. The cyclic voltammetry showed reversible reductions for the C^N^N complexes, with markedly fewer negative potentials (around −1.6 V vs. ferrocene) for the complexes containing the naphen ligand compared with the thnaphen derivatives (around −1.9 V). With irreversible oxidations at around +0.3 V for all of the complexes, the naphen made a difference in the electrochemical gap of about 0.3 eV (1.9 vs. 2.2 eV) compared with thnaphen. The bdq complex was completely different, with an irreversible reduction at around −2 V caused by the N^C^N coordination pattern, which lacked a good electron acceptor such as the phenanthroline unit in the C^N^N ligand naphen. Long-wavelength UV-Vis absorption bands were found around 520 to 530 nm for the C^N^N complexes with the C≡CPh coligand and were red-shifted when compared with the Cl derivatives. The N^C^N-coordinated bdq complex was markedly blue-shifted (493 nm). The steady-state photoluminescence spectra showed poorly structured emission bands peaking at around 630 nm for the two naphen complexes and 570 nm for the thnaphen derivatives. The bdq complex showed a pronounced vibrational structure and an emission maximum at 586 nm. Assuming mixed 3LC/3MLCT excited states, the vibronic progression for the N^C^N bdq complex indicated a higher LC character than assumed for the C^N^N-coordinated naphen and thnaphen complexes. The blue-shift was a result of the different N^C^N vs. C^N^N coordination. The photoluminescence lifetimes and quantum yields ΦL massively increased from solutions at 298 K (0.06 to 0.24) to glassy frozen matrices at 77 K (0.80 to 0.95). The nanosecond time-resolved study on [Pt(naphen)(Cl)] showed a phosphorescence emission signal originating from the mixed 3LC/3MLCT with an emission lifetime of around 3 µs.